2017
DOI: 10.1007/s00038-016-0937-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pediatric HIV-1 patients treated with first-line antiretroviral therapy in Vietnam: a nested case–control study

Abstract: There is an inherent complexity within clinical markers that is challenging to determine HIV-pediatric failure and further research is needed to build a complete picture to guide clinical, evidence-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Accordingly, multiple factors need to be considered and collectively illustrate the complexity of individualized HIV therapy. While the characteristics of drugs and the virus are well studied and mostly considered in treatment options [ 5 , 6 ], host characteristics are less well understood [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, multiple factors need to be considered and collectively illustrate the complexity of individualized HIV therapy. While the characteristics of drugs and the virus are well studied and mostly considered in treatment options [ 5 , 6 ], host characteristics are less well understood [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]12 In a cohort of 266 HIV-infected children with suspected tuberculosis (TB) in four countries (Burkina Faso, Cambodia, Cameroon, and Vietnam), Marcy et al found that TB, young age, CD4 less than 10%, miliary features, and elevated serum transaminases were all independent predictors of mortality. 13 In Vietnam, by the end of 2011, there were 3200 Vietnamese children with HIV/AIDS receiving ART; However, there were a few reports on ART outcomes among HIV-infected children [14][15][16] In a study of 86 children on ART in Hanoi, Vietnam, Pham et al reported that the success rate (plasma HIV-1 viral load <1000 copies/mL) was 79.1% after 2-year follow-up. 14 As far as this author knows, no studies to evaluate long-term ART outcomes for infected-HIV children have been conducted in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Using multivariable regression, we found a strong correlation between HAZ and CD4 T‐cell count, and between HAZ and CD4 T‐cell percentage. We have shown that CD4 T‐cell count and CD4 T‐cell percentage have a great advantage in the prognosis of TF; therefore HAZ might be a good marker to monitor treatment response. In addition, height could be the most sensitive growth marker in the monitoring of disease progression.…”
Section: Discussionmentioning
confidence: 99%